Supplement Consumption and Facial Care Products on Acne Vulgaris: A Cross-Sectional Study Among Medical Students - Aras, Dara Ugi; Wahyuni, St. Nurul Rezki; Adam, Adriyanti; Arif, Sitti Musafirah; Viviani L. (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Signs of acne vulgaris, a condition of widespread inflammation in pilosebaceous units, include blackheads, papules, pustules, and nodules. Acne vulgaris affects 85% of teenagers and young adults between the ages of 12 and 15. Acne vulgaris is primarily caused by hyperkeratinization of the pilosebaceous ducts, inflammation, mycobacterial infection, and excessive sebum production. The term dysseborrhea refers to the changes in sebum levels that happen during puberty, both in terms of quantity and quality. Apart from exogenous factors such as cosmetics and comedogenic medications, endogenous elements such as hormones and genetics can also contribute to the issue. The aim of this study is to investigate the relationship between the use of face care products and supplementation and the incidence of acne vulgaris in medical students at the University of Muhammadiyah Makassar (Unismuh). Methods. For the study, a cross-sectional technique was used. The sample method used is simple random sampling. A sixteen-item questionnaire was used to gather data, which the Chi-Square test was then used to analyze. Results. The analysis yielded two significant results, a value of p=0.552 (p>0.05) showed no significant correlation between the incidence of acne vulgaris and the use of face products, and a value of p=0.132 (p>0.05) showed no significant correlation between the incidence of acne vulgaris and consumption of supplements. Conclusion. There is no correlation between consuming vitamins and using face care products to stop pupils from getting acne vulgaris.